The Influence of Organizational Culture, Leadership Member Exchange, and Compensation on Happiness at Work of Millennial and Gen Z Generations at PT Bank Tabungan Negara (Persero) Tbk Regional Loan Processing Center 1 - Ilham, Ziqri Nur; P. Winarto, Oetami (Dinasti Publisher, 2025)
The aim of this study is to analyze the relationship between organizational culture, leadership style (Leader-Member Exchange), compensation, and happiness at work among millennial and Gen Z employees at PT Bank Tabungan Negara (Persero) Regional Loan Processing Center 1, West Java. This study employs a quantitative research design to analyze the relationships between organizational culture, leadership style (Leader-Member Exchange), compensation, and happiness at work among millennial and Gen Z employees at PT Bank Tabungan Negara (Persero) Regional Loan Processing Center 1, West Java. The data collection methods include internet-based surveys and a literature review. The study sample consists of 131 permanent employees, with a saturated sampling technique. The data were analyzed using descriptive statistics and Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) to test the relationships between variables.Based on the analysis results, this study concludes that organizational culture, compensation, and Leader-Member Exchange (LMX) significantly influence happiness at work among millennial and Gen Z employees at PT Bank Tabungan Negara (Persero) Regional Loan Processing Center 1. Increases in organizational culture, compensation, and LMX are positively related to happiness at work. LMX also serves as an intervening variable that strengthens the impact of organizational culture and compensation on happiness. LMX is the highest indicator with the most significant influence on happiness at work, while organizational culture has the lowest influence.